Interference with anti-trypanosome immune responses in rabbits infected with cyclically-transmitted Trypanosoma congolense - LUCKINS, A.G.; GRAY, A.R. (Wiley, 1983)
Summary Rabbits were infected with two clones of antigenically distinct stocks of Trypanosoma congolense transmitted through Glossina morsitans. Local skin reaction development and the appearance of neutralizing antibodies were followed in animals infected with one or other of the trypanosome stocks, with both stocks simultaneously or with both stocks consecutively. There was little difference in local skin reaction development on rabbits infected with a single stock or with both stocks simultaneously but, in rabbits exposed to a heterologous stock 14 or 21 days after a primary infection reactions were reduced in size or completely absent. Neutralizing antibodies against metacyclic‐derived trypano‐somes were detected 21 days after infection in animals infected with a single trypanosome stock and, in rabbits infected with both stocks simultaneously, antibodies against each stock were also detected 21 to 28 days after infection. In rabbits challenged 14 or 21 days after primary infection the appearance of trypanocidal antibodies against the stock used for challenge was delayed from 28 to 49 days.